Pengaruh Kepemimpinan Transformasional Dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai - Ninda Nur Utami; Widya Parimita; Suherdi Suherdi (Jurnal Indonesia Sosial Sains, 2023)
This study aims to determine and analyze the positive and significant influence of transformational leadership and the work environment on the job satisfaction of regional secretariat employees in Magelang City. The research method uses quantitative research with multiple regression analysis and data collection techniques carried out online through questionnaires. The results of the study revealed that transformational leadership had a significant effect on the job satisfaction of regional secretariat employees in the city of Magelang with a count of 2.300 > t table of 1.660. Second, the work environment has a significant effect on the job satisfaction of regional secretariat employees in Magelang City with a t count of 9.337 > t table of 1.660. Third, transformational leadership and the work environment significantly influence the job satisfaction of regional secretariat employees in Magelang City with an f count of 71.908 > f table of 3.09. The conclusion of this study is that there is a positive and significant effect of transformational leadership and the work environment on the job satisfaction of regional secretariat employees in Magelang City.